Des sons pour de nouveaux Espaces: A l’écoute de Bachelard - Mota, Marcus (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
In this paper, I offer a rereading of Gaston Bachelard’s L’expérience de l’espace dans la physique contemporaine (1937) in order to demonstrate how physical phenomena are constructed and interpreted in a way close to sound-oriented events. After this rereading, I present some musical experiments that explore some concepts that were discussed previously so as to provide an aesthetic counterpoint to the new concept of reality developed by new physics.